+0  
 
0
268
2
avatar+299 

Use the laws of exponents to simplify each of the following. Give your answer using only positive exponets.

 

2^2/3     2^-5/4

 Jan 18, 2019
 #1
avatar+106532 
+1

 

 

 

2^(2/3) =  (2^2)^(1/3)  = (4)^(1/3) 

 

2^(-5/4)

 

Note that this is  (2/1)^(-5/4)

 

We can "flip" the fraction and make the exponent positive.....so we have

 

(1/2)^(5/4)  =   [(1/2)^5 ] ^(1/4)   =  [ 1/32 ]^(1/4)   

 

 

The last answer might also be simplified as    [ (1/16) (1/2) ]  ^(1/4)  =  

 

(1/16)^(1/4) * (1/2)^(1/4) =

 

(1/2)* (1/2)^(1/4)

 

cool cool cool

 Jan 18, 2019

6 Online Users